Analisis Pengaruh Brand Awareness dan Brand Image terhadap Brand Equity serta Implikasinya terhadap Minat Pembelian - Sindy Maulidiya (CV. Satria Jaya, 2024)
This study aims to analyze the influence of Brand Awareness and Brand Image on Brand Equity and its implications on consumer buying interest in Rabbani products. The approach used in this study is a quantitative method through a survey with questionnaire instruments in the sampling process. The research sample consisted of 100 respondents who were consumers of Rabbani veils in the Pasuruan Regency area. The data analysis technique was carried out using Partial Least Square (PLS) through the WarpPLS application version 7.0. The results of the study show that Brand Awareness has a positive and significant effect on Brand Equity, as well as a positive and significant effect on Buying Interest. Furthermore, Brand Image also has a positive and significant effect on Brand Equity, but its influence on Buying Interest is positive but not significant. Brand Equity has been proven to have a positive and significant influence on Buying Interest